Microstructure investigation of hydrothermal damage of aged SMC composites using Micro-computed tomography and scanning electron microscopy. (March 2021) - Abdessalem, Abir; Tamboura, Sahbi; Fitoussi, Joseph; Daly, Hachmi Ben; Tcharkhtchi, Abbas; Meraghni, Fodil
Highlights: The moisture diffusivity follow the Langmuir type diffusion. The crack density and crack length increase with ageing parameters (time and temperature). Interfacial cracks are shown to be the most destructive phenomenon. Abstract: This paper presents an investigation on the effects of hydrothermal aging on Sheet Molding Compound (SMC) composite. Two different techniques were carried out to study the inner structure of aged SMC composite. Firstly, X-ray micro computed tomography (XµCT) was used to evaluate the changes using 3D images. The results showed cracks in all the composite structure with different shapes and volume in response to the hydrothermal conditions. The cracks results from the build up of an osmotic pressure in microcavities, which is proportional to water concentration. However, it was not possible to quantify separately the hydrothermal induced damage in the studied SMC composite material. Therefore, the XµCT analyzes were supplemented by a microscopic study. This step has been studied in terms of crack density evolution and crack propagation rate. The results obtained by XµCT technique and SEM observations show that the damage increases continuously with time and temperature during aging. The damage was found to be located in the voids contained in the matrix at early stage of aging. Then it is mostly developed into the fiber interface in the form of fiber/matrix interfacial debonding.